Architecture in Context : Designing in the Middle East (UK; Wiley, 2017)
Architects are building in the Gulf and across the Middle East as if there were no context. The iconic abstract architecture that dominates current worldwide architectural discourse and practice is being replicated across the Middle Easet, even in countries that have a rich architectural past and vibrant contemporary urban landscapes. Students of architecture and practising architects in the region are also being taught from solely foreign historicist or modernist surveys that may not be directly relevant to the context in which they are designing. This book explores the environmental significance, cultural meaning and design vocabularies of architecture across the region. Architecture in Context: Designing in the Middle East provides a foundation for understanding the critical context of architecture and design in this region. It does this by: - presenting a practical overview of architectural know-how in the Middle East, and its potential for cultivating a sense of place - introducing local architectural vocabularies and styles, and how they can still be reactivated in contemporary design - exploring the cultural and contextual meaning of forms as references that may influence contemporary architecture - discussing important discourses and trends in architecture that allow a rethinking of the current global/local dichotomy.Highly illustrated, the book covers architecture and design in North Africa, the Levant, the Gulf, and Turkey, Iran and Iraq.
English
Keywords: NA2695-2793 Architectural Drawing and Design